Studying the Effect of Magnetron Copper Deposition on the Surface Topography of Biodegradable Antibacterial Coating. - Bauyrzhan, Maratuly; Azamatov, Bagdat Nurlanovich; Jes, Alexey Vladimirovich (Avicenna Journal of Medical Biotechnology)
Background: The surface properties of the materials used significantly influence the success and longevity of medical implants. Increasing surface roughness promotes osteoblast activity and osseointegration, while biodegradable materials such as copper have shown potential for antimicrobial applications. However, the effect of coating parameters on surface topography is not well investigated. Methods: Sputtering of copper was performed using EPOS-PVD-440 system (Zelenograd, Russia). The samples were examined by Scanning Electron Microscopy (SEM) with subsequent image processing in Mountains software (Digital Surf). Antibacterial efficacy was evaluated against Staphylococcus aureus by measuring the zone of inhibition. Additionally, copper ion release was monitored over time to assess its correlation with changes in surface topography. Results: Higher sputtering currents increased surface roughness and particle size, with a significant release of copper ions within the first 24 hr of immersion. Samples sputtered at higher currents exhibited coarser grain structures. The release of copper ions in the simulated biological environment led to further changes in surface topography, high-lighting the critical influence of sputtering parameters on coating properties. Conclusion: Optimizing magnetron copper deposition parameters enhances the surface topography and antibacterial effectiveness of biodegradable coatings on implants.